Scientometrics and Intellectual Production Assessment - López López, Wilson; Pontificia Universidad Javeriana (2009)
Scientometrics has finally reached the importance it deserves in Iberoamerica with regards to the assessment of research productivity. This renewed vision of this discipline has been associated to a couple of factors. First, the emergence of assessment systems for productivity, visiblity and quality of Universities: World, Regional and National Rankings. Second, that policymakers are using these rankings to make decisions, and third, even critics are using them to question or show knowledge communication and production practices (loaded with ideology). Many questions have been stated by the debate about these rankings, specially with regards to the ability of the indicators. For example, the Times Ranking (http://www.timeshighereducation.co.uk/index.asp?navcode=92) shows the following weights: 60% for research quality (articles in ISI and SCOPUS first-level journals), 10% for the students’ ability to find jobs, 10% for international collaboration, 20% for the relationship between students and Faculty; or the Shanghai Jiao Tong University Ranking (http://www.arwu.org/) which has a different balance: 10% for number of Nobel prizes, 20% for Fields Medal recipients, 20% for researchers with high citation indexes in 21 general topics in ISI, 20% for number of articles in Science or Nature, 20% for ISI contributions impact. There is a clear bias in these rankings, since only some Universities will be included in them and take the first places. Recently, the Scimago Research Group (http://www.scimagojr.com/) introduced a new ranking (http://www.magisnet.com/pdf/Ranking- MundialUniversidades.pdf) which, unlike others, does not depend on production but on received citations in the SCOPUS database (which has the largest coverage in languages and countries). It is clear that there is another citation data arsenal available for those who want to have some information on the usage of scientific knowledge through journals, is the CROWN index, which measures the normalized impact of journals in a certain area. This ranking is able to compare against areas, regions or countries, as well as identifying several knowledge production indicators. Nevertheless, despite all the discussions about the rankings, the truth is that they end up arising questions for academic communities in Iberoamerica. First, the question about the strategic priority that will be given to research in the Universities, and second, the dimension of the investment and the structural changes that the institution is willing to implement in terms of management, research, hiring educators with an emphasis on research and services, an incentive system for intellectual production, the visibility of research (multilevel communication strategies for peers and non-expert communities) and academic marketing, among others. There seems to be no discussion regarding the value held by scientific communication, specially scientific journals, in the assessment of the recongnition made by academics and expressed in how they cite each other in their works, and as I said before, the importance of scientometric analysis for the understanding of scientific dynamics. Universitas Psychologica is now included in the two databases that generate citation indicators (ISI and SCOPUS). The commitment of our community is now more complex and difficult, since a good assessment of the journal will be achieved through the analysis of how its documents are used in citations. This task requires the commitment of writers and researchers that have collaborated with the journal. Wilson López-López Editor